2010
DOI: 10.1007/s00417-010-1434-6
|View full text |Cite
|
Sign up to set email alerts
|

Rubella virus as a possible etiological agent of Fuchs heterochromic iridocyclitis

Abstract: Our laboratory data strongly suggest a relationship between FHI and rubella virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 22 publications
2
46
0
2
Order By: Relevance
“…Rubella virus infection was diagnosed by detection of intraocular antibody production solely, which is similar to previous results. 4,[27][28][29] The clinical sensitivity of PCR and GWC is difficult to assess, as there is no official gold standard defined for these viral uveitis entities. However, from literatures, it is known that PCR has a sensitivity of up to 81% in detecting VZV or HSV in herpetic AU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rubella virus infection was diagnosed by detection of intraocular antibody production solely, which is similar to previous results. 4,[27][28][29] The clinical sensitivity of PCR and GWC is difficult to assess, as there is no official gold standard defined for these viral uveitis entities. However, from literatures, it is known that PCR has a sensitivity of up to 81% in detecting VZV or HSV in herpetic AU.…”
Section: Discussionmentioning
confidence: 99%
“…5 For Rubella virus, it has been reported consistently that the GWC is positive in virtually 100% of FHUS cases and that this virus is also strongly associated with incomplete cases of FHUS; PCR is of little value for the diagnosis of Rubella virus associated uveitis. 4,5,26,28,29 It has been shown that the sensitivity of diagnostic tests was influenced by the time interval between the onset of symptoms and sample collection. 9 Our study included an insufficient number of patients to investigate these associations.…”
Section: Discussionmentioning
confidence: 99%
“…What triggers inflammation in FHI is still not known; Rubella virus, Toxoplasma gondii, and cytomegalovirus have all been identified as the probable triggers (Suzuki et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki et al [74] demonstrated significant intraocular synthesis of rubella virus antibodies (GWC [ 3) in all ten of the Japanese patients with FHI which were tested, but not in the control group (n = 8); moreover, the rubella genome was detected by nested reverse transcription (RT)-PCR in two of nine patients (22%) tested. Taken together, these laboratory data strongly suggest a relationship between FHI and the rubella virus.…”
Section: Rubella Virusmentioning
confidence: 99%